RANCANG BANGUN MEJA SERBAGUNA MINIMALIS - Adi Dwi Pramana; Muhamad Zainudin; Gilang Rusadi Ahmad (Narada : Jurnal Desain dan Seni, 2021)
The minimalist multipurpose table design aims to provide comfort for people who use it. As a society, of course, we need a product that not only has one function, but also has other functions that can make our daily life easier. This minimalist multipurpose table design aims to produce a product that can be used in a workspace that has a function for studying, doing office tasks, and so on. Besides that there are shelves that are used to place books, decorations, and so on. Data collection methods used for the preparation of this research report include primary data sources consisting of observations, and also through secondary data sources. The design process is carried out through several stages including measuring, cutting, welding, polishing, coloring, and assembling until the table is ready for use. Minimalist multipurpose table frame made of iron and wood with a shelf height of 115 cm, a table height of 75 cm, and distance between the two table legs 120 cm, and a table leg width of 50 cm.